AMALAN KESELAMATAN PELAJAR DALAM BENGKEL KATERING - Ismail, Mohd Erfy; Hashim, Suhaizal; Marian, Mohd Fairuz; Rahim, Mohd Bekri; Amin, Faizal; Yunus, Nur; Masran, Saiful Hadi (Online Journal for TVET Practitioners, 2018)
In the field of Technical & Vocational Education Teaching (TVET), most of the teaching and learning processes were through practical methods or also known as "hands-on" at workshop or laboratory. The diversity of modern and sophisticated equipment requires an adequate of security management because the work done in the workshop is vulnerable to the risk of accidents if safety condition been ignored. Therefore, the survey was carried out on the perception, knowledge and attitude of catering programme students at Muar Vocational College (VC) on safety at the workshop. The population and sample in this study were 90 respondents consisting of male and female students. The respondents of this study were catering programme students from year one to fourth which involve the entire population of the study who conducting practical work in the workshop. The instrument used is in the form of questionnaire to get the information. The data obtained were collected and analyzed descriptively using SPSS (Statistical Package for The Social Sciences) version 21. Based on the pilot study, the reliability value of the instrument is 0.91 and it shows the reliability of the instrument is high. The findings show that good safety practices produce positive effects and influence on students' knowledge, attitudes and perceptions. Additionally, studies show that the attitudes of practicing a safe and orderly work culture can create a disciplined and accountable attitude.